Current knowledge and development of hederagenin as a promising medicinal agent: a comprehensive review. Issue 43 (3rd July 2018) - Zeng, Jia; Huang, Ting; Xue, Man; Chen, Jianxing; Feng, Linglin; Du, Ruofei; Feng, Yi
Abstract : Hederagenin (HG) is a pentacyclic triterpenoid that exists in many plants in the form(s) of sapogenin or saponins. Abstract : Hederagenin (HG) is a pentacyclic triterpenoid that exists in many plants in the form(s) of sapogenin or saponins. This review highlights the pharmacokinetics, pharmacological activities, mechanisms of action, and safety of HG using literature and patents from the last 50 years to collate information on this compound as a promising medicinal agent. This review also looks at the development of related derivatives of HG with increased efficacy and lower toxicity. HG is quickly absorbed in the gastrointestinal tract with a short elimination half-life, and can cross the blood–brain barrier and rapidly distribute into cerebrospinal fluid. HG has been shown to possess a wide range of pharmacological activities, including anti-tumor, anti-inflammatory, anti-depressant, anti-neurodegenerative, anti-hyperlipidemia, anti-diabetic, anti-leishmanial, and anti-viral activity. In particular, the extensive anti-tumor activity indicates that HG has the potential to be a highly effective chemotherapy agent. Recently, in the search for more active compounds as potential pharmaceuticals, structural modification of the triterpene scaffold of HG at the C-3, C-12, C-13, C-23, and C-28 positions, has resulted in compounds that exhibited greater potency than HG itself. However, the low bioavailability and moderate hemolysis effect of HG may limit its clinical application. The cause of the observed toxic effects in some animals, including dogs, cats, cattle, goats, and horses also needs to be explained. Future studies of HG focusing on extending the half-life, improving bioavailability, enhancing pharmacological activity, as well as decreasing or avoiding hemolysis by structural modification or formulation design could potentially accelerate HG from the preclinical to clinical research phase.